Metabolic engineering of erythritol production from glycerol by Yarrowia lipolytica - Wang, Ya-Ting; Zhao, Ling-Xuan; Wei, Liu-Jing; Chen, Jun; Liu, Zhijie; Liu, Feng; Hua, Qiang (Biotechnology and bioprocess engineering, 2024)
Erythritol as a four-carbon polyol has been widely used in food, pharmaceutical and daily chemical industries with characteristics of low caloric value and high chemical stability. Here, a system metabolic engineering strategy was used to increase the yield of erythritol from glycerol in Yarrowia lipolytica by enhancing the substrate transformation and restricting the by-product synthesis. Specifically, we determined that over-expression of a newly identified erythrose reductase YPR1 was able to improve the erythritol production as same as the well-known erythrose reductase ER27. Instead of its up-regulation, knockout of erythrose reductase ER10 was effective to improve erythritol synthesis. Moreover, both over-expression of YPR1 and deletion of ER10 significantly accelerated the glycerol utilization in response to high osmotic stress. To further decrease the by-product accumulation, a restriction and recycling strategy was implemented by knockout of mannitol dehydrogenase MDH2 and enhancement of arabitol dehydrogenase ADH1 and fructokinase HXK1. The engineered strain YL13 produced a titer of 25 g/L erythritol and less than 0.5 g/L mannitol and arabitol. By over-expression of transketolase TKL1, the final strain YL14 produced 28.5 g/L erythritol and none of mannitol and arabitol. This study provides a new idea for reducing the production of by-products and improving the glycerol conversion to erythritol.